Penguatan Perlindungan Anak Kota Bandung Dalam Perspektif Collaborative Governance - Alpin Alpin; Fajar Tri Sakti; Mohamad Ichsana Nur (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2022)
Child protection has been an effort to guarantee and protect children to be able to live, grow and develop with their rights and dignity. However, nowadays there are many incidents of neglecting children, wrong parenting patterns, trafficking, and sexual, physical, and then psychological violence into common problems requiring various parts. Therefore, to follow up, the government must deal with it by collaborating with various stakeholders. This study aims to analyze how the collaboration built by the government and other stakeholders in the prevention and realization of Child-Friendly Cities. The method used in this research is a qualitative approach and a descriptive method. The techniques collection data used in this observation that was in-depth structured interviews with resource persons, and a literature study. The results of this study indicate that the application of strengthening child protection in the city of Bandung between the government and the other stakeholders has shown conformity with the concept of Collaborative Governance although there are some shortcomings in was implementation.